Software development methodologies and practices in start‐ups. Issue 6 (1st December 2019) - Tegegne, Esubalew Workineh; Seppänen, Pertti; Ahmad, Muhammad Ovais
Abstract : Software start‐ups are aiming to develop cutting‐edge software products under highly uncertain conditions, overcoming fast‐growing markets under multiple influences. This study aims to identify and analyse the existing scientific literature regarding software development methodologies and practices in software start‐ups published between January 2006 and December 2017 using the systematic mapping study. The results identified 37 relevant primary studies out of 1982 papers. To validate the results from the mapping study, an empirical study was based on the research data collected from 14 real‐life software start‐ups located in Finland, Italy and Norway. The result shows that Agile and Lean start‐up methodologies are the most commonly used in software start‐ups due to the flexible nature and easy tailoring. A total of 144 software development work practices are extracted from the primary studies. This study contributes to the research in several ways: (i) provides state of the art regarding software development methods and practices in software start‐up contexts, (ii) reports commonly used methods along with its benefits identified in primary studies and (iii) identifies opportunities for future software start‐up research.